2015
DOI: 10.1002/art.38949
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled, Twelve‐Week, Dose‐Ranging Study of Decernotinib, an Oral Selective JAK‐3 Inhibitor, as Monotherapy in Patients With Active Rheumatoid Arthritis

Abstract: Objective. To assess the efficacy and safety of oral decernotinib (VX-509; Vertex Pharmaceuticals) monotherapy in a 12-week, randomized, double-blind, placebo-controlled, dose-ranging study of patients with rheumatoid arthritis (RA).Methods. Two hundred four adults with active RA who had been unsuccessfully treated with >1 diseasemodifying antirheumatic drug were administered placebo tablets or decernotinib twice a day at dosages of 25 mg, 50 mg, 100 mg, or 150 mg. Primary measures of efficacy at week 12 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 29 publications
8
60
0
2
Order By: Relevance
“…2B). This overlap is consistent with reported efficacy in early RA trials for both JAK1i and a reported JAK3i-biased inhibitor (8,29,30). There were, however, quantitative differences between signatures of isoform-specific JAKi (e.g., JAK1i remains more effective than JAK3i at inhibiting ISGs), and the comparative effect of JAK1i and JAK3i on the IL-2 response varies with dosage.…”
Section: Discussionsupporting
confidence: 86%
“…2B). This overlap is consistent with reported efficacy in early RA trials for both JAK1i and a reported JAK3i-biased inhibitor (8,29,30). There were, however, quantitative differences between signatures of isoform-specific JAKi (e.g., JAK1i remains more effective than JAK3i at inhibiting ISGs), and the comparative effect of JAK1i and JAK3i on the IL-2 response varies with dosage.…”
Section: Discussionsupporting
confidence: 86%
“…Patients treated with VX-509 experienced mild but consistent dose-dependent increases in alanine aminotransferase, aspartate aminotransferase and creatine kinase. The increases in cholesterol and liver enzymes in patients receiving VX-509 in this study were similar to those observed in prior studies 10 11…”
Section: Resultssupporting
confidence: 90%
“…Dose-dependent responses were observed for DAS28-CRP and DAS28-ESR scores, ACR response and RAMRIS scores for synovitis and osteitis. No new safety concerns developed, and treatment was generally well tolerated, with an AE profile similar to that previously seen for this agent 10 11. These findings complement those of phase II studies that demonstrated the efficacy and safety of VX-509 as monotherapy10 and in combination with methotrexate in patients with RA 11…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…32 Moreover, a reportedly selective Jak1 inhibitor, GLPG0634, also met its primary endpoint in a phase IIa RA trial with no anaemia and no lipid abnormalities observed. 33 CEP-33779, a selective Jak2 inhibitor, showed efficacy in two preclinical arthritis models.…”
Section: Other Jakinibsmentioning
confidence: 99%